2011
DOI: 10.1017/s0714980810000772
|View full text |Cite
|
Sign up to set email alerts
|

Le choix de traitement en triade incluant un patient âgé apte en soins palliatifs : à la recherche d’un modèle théorique

Abstract: The elderly in palliative care are confronted with difficult decisions relating to treatments. The philosophy of palliative care, namely, including the patient and his/her family right away, leads the doctor to consult with the two parties involved when choosing a treatment. As no theoretical model allows us to understand how the decision-making process hinges on the trio (a capable elderly person, a family caregiver, and the doctor) in a context of palliative care, we propose one which was developed from thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(125 reference statements)
0
0
0
Order By: Relevance
“…In their study on palliative care, Lamontagne et al (2011) concluded that the healthcare choice decision largely depends on the self-efficacy of the arrangement of overall care provision [39]. In the current study, the authors have examined the different aspects of understanding comprehensive care and explored the self-efficacy items that significantly contribute to treatment choice.…”
Section: Role Of Self-efficacy Beliefsmentioning
confidence: 92%
“…In their study on palliative care, Lamontagne et al (2011) concluded that the healthcare choice decision largely depends on the self-efficacy of the arrangement of overall care provision [39]. In the current study, the authors have examined the different aspects of understanding comprehensive care and explored the self-efficacy items that significantly contribute to treatment choice.…”
Section: Role Of Self-efficacy Beliefsmentioning
confidence: 92%